Methodology For Developing Students’ Creative Thinking Through Graphic Assignments - Sherov Dilshod Reyimberganovich; Boltaboyeva Nafisa Hayitboy qizi (Academia One, 2026)
This article analyzes the theoretical and practical aspects of developing students’ creative thinking through graphic assignments in higher education. The methodology of enhancing cognitive activity through visual tasks, creative exercises, and problem-solving approaches is discussed. The integration of modern pedagogical technologies into graphic education is also explored.
Keywords: graphic assignments; creative thinking; fine arts; engineering graphics